Improvement of corrosion resistance of aisi 410 martensitic steel using plasma coating. (2018) - Girisha, K.G.; Sreenivas Rao, K.V.
Abstract: Historically, coating has been developed to give a shield against erosion, wear and corrosion to secure a material from its harsh working environment. The objective of this work is to study the corrosion behavior of the Ni/Cr pre coated plasma sprayed TiO2 coatings on AISI 410 steel using salt spray technique as per ASTM B117 standard. Investigation of corrosion behavior was carried out at different exposure time (50, 100, 150, 200hrs) in 5% NaCl solution. Coatings were characterized by Scanning Electron Microscope (SEM) micrographs, Optical Microscope (OM) and EDX analysis. Vickers micro hardness test and porosity of the coated surface was also determined. Experimental results confirm that, TiO2 coatings have high corrosion resistance which can be attributed to high micro hardness and less porosity (2-3%) as compared to un-coated steel substrates.